Inventions of Sexuality in Kathleen Winter’sAnnabel - Neuhaus, Mareike (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Kathleen Winter’s novel Annabel ends the relative silence about intersexuality in Canadian literature while simultaneously challenging the discourses of science, religion, and law that have helped produce this silence. Tracing Wayne’s journey from a peripheral existence within a heterotopia of deviation to a life-affirming presence, Annabel employs various strategies to present its readers with two interrelated stories: the story of Wayne Blake and the story of what would need to happen – or change in our societies – for Wayne’s personhood to be recognized by others. The ideas of Henri Lefebvre, Michel Foucault, and Judith Butler can help construct a framework for understanding the complex interarticulation of space and sexuality in this text. In the end, the novel asks us all, in the name of non-violence, to accept difference as a necessary challenge to dominant understandings of the human; in the process, it raises important questions that cannot be dealt with by queer theory alone.